ANALISIS SEKTOR EKONOMI BASIS DAN PERANANNYA TERHADAP KETIMPANGAN PENDAPATAN ANTAR KABUPATEN/KOTA DI PROVINSI RIAU TAHUN 2010 – 2017 - Ridho, Muhammad Habib; Hamidi, Wahyu; Taryono, Taryono (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2019)
This study aims to analyze the basic economic sector and its role inincome inequality between districts / cities in Riau Province. Then the secondarydata used in this study for the period 2010 to 2017 sourced from BPS in RiauProvince and analyzed by Location Quotient (LQ) and Wiliamson Index Sectoral.The results showed that based on LQ Analysis with the Income approach ofdistricts / cities in Riau Province had 3 basic economic sectors, namely theAgriculture, Forestry, and Fisheries Sector, the Processing Industry Sector andthe Services Sector. Then based on LQ Analysis with the labor approach ofdistricts / cities in Riau Province only have 1 economic sector base, namely theAgriculture, Forestry and Fisheries Sector. Furthermore, the base sector that hasavarage sectoral income inequality with a low category is the Agriculture Sector(0.25) and the Services Sector (0.26), and the average sectoral income inequalitywith the medium category is the Processing Industry Sector (0, 47).Keywords: Base Economic Sector, Location Quotient, InequalitySectoralRevenue, Sectoral Wiliams Index